2012
DOI: 10.1177/039463201202500303
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and Cancer Prevention

Abstract: Cancer cells invade surrounding tissues and metastasize to distant sites. Diet high in fat is a strong link to, and perhaps causes, a high incidence of tumours. Trans-fatty acid might impair the function and it could be involved in the development of cancer. Cholesterol is also strongly suspected to be involved in the development of tumours, therefore it is important for everyone to eat well, especially for people with cancer to prevent the body tissues from breaking down and helping to rebuild the normal tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
20
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…In this study, an HFD containing high amounts of PA influenced MIC1 expression and promoted PCa progression. These findings support the view that altered cytokine levels and signaling influenced by FA dietary content may play a significant role in PCa progression (Tete et al 2012). …”
Section: Discussionsupporting
confidence: 86%
“…In this study, an HFD containing high amounts of PA influenced MIC1 expression and promoted PCa progression. These findings support the view that altered cytokine levels and signaling influenced by FA dietary content may play a significant role in PCa progression (Tete et al 2012). …”
Section: Discussionsupporting
confidence: 86%
“…Inflammation in the body may play a role in cardiovascular disease and cancer [51]. Because dietary intake can have a significant impact on inflammatory markers [7,8] and observational research has shown that vegetarians have lower levels of CRP than nonvegetarians [12,13], adoption of plantbased dietary approaches may be a potential strategy for reducing inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Natural compounds, such as epigallocatechin-3-gallate (EGCG), resveratrol, lycopene, polyunsaturated omega-3 fatty acids (PUFA) and genistein, were reported to exert antitumor effects on several cancer cell lines89. These compounds were also shown to possess chemopreventive activity and to potentiate the antitumor effects of standard treatments1011.…”
mentioning
confidence: 99%